2011
DOI: 10.1038/jhg.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of contiguous X-chromosome deletion syndrome encompassing the BTK and TIMM8A genes

Abstract: Patients with X-linked agammaglobulinemia (XLA) can present with sensorineural deafness. This can result from a gross deletion that not only involved the Bruton's tyrosine kinase (BTK) gene, but also TIMM8A, mutations in which underlie the MohrTranebjaerg syndrome (MTS). We analyzed the genomic break points observed in three XLA-MTS patients and compared these with deletions break points from XLA patients. Patient 1 had a 63-kb deletion with break points in intron 15 of BTK and 4 kb upstream of TAF7L. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The four patients described with the microdeletion spanning BTK, TIMM8A, TAF7L and DRP2 presented the typical X-linked agammaglobulinaemia and Mohr-Tranebjaerg syndrome phenotypes, but also autism and language delay. [43][44][45] Interestingly, a recent WES study reported the same mutation (E432*) that we found in DRP2 in one autistic family, which was absent from a large cohort of controls. 18 This work represents one of the first comprehensive studies of multiplex families with ASD by exome sequencing.…”
Section: Discussionsupporting
confidence: 48%
“…The four patients described with the microdeletion spanning BTK, TIMM8A, TAF7L and DRP2 presented the typical X-linked agammaglobulinaemia and Mohr-Tranebjaerg syndrome phenotypes, but also autism and language delay. [43][44][45] Interestingly, a recent WES study reported the same mutation (E432*) that we found in DRP2 in one autistic family, which was absent from a large cohort of controls. 18 This work represents one of the first comprehensive studies of multiplex families with ASD by exome sequencing.…”
Section: Discussionsupporting
confidence: 48%
“…This 879aa protein is encoded by a 45kb gene localized to Xq22 and was originally described as being expressed principally in the brain and spinal cord [21]. Deletions spanning DRP2 alongside other X-linked genes such as BTK have been reported with agammaglobulinaemia and Mohr–Tranebjaerg syndrome [22-24]. More recently, DRP2 truncating mutations have been proposed as a potential cause of autism spectrum disorder though the mechanism remains to be elucidated [25].…”
Section: Discussionmentioning
confidence: 99%
“…The human genome project hg18 identified 584 human reference-specific Alu insertions [43]. Alu insertion can influence the genome stability, and it accounts for 0.1% of all human genetic disorders [9] such as hereditary desmoid disease [50], cystic fibrosis [51], Dent's disease [52, 53], X-linked agammaglobulinemia [5457], hemophilia A and B [5860], autoimmune lymphoproliferative syndrome [61], Apert syndrome [62], neurofibromatosis type 1 [63], benign isolated glycerol kinase deficiency [64], hyper IgM with immunodeficiency syndrome [65], Menkes disease [66], Alstrom syndrome [67], retinitis pigmentosa [68], acholinesterasemia [69], autosomal dominant optic atrophy [70], hemolytic anemia [24], autosomal branchio-oto-renal syndrome [71], acute intermittent porphyria [72], mucolipidosis II [73], and several type of cancer [23, 74–77] to cite a few. There are several mechanisms by which Alu can alter genomic structure.…”
Section: Alu-mediated Recombination and Insertional Mutagenesis Comentioning
confidence: 99%